2017
DOI: 10.1039/c7ra02682j
|View full text |Cite
|
Sign up to set email alerts
|

A silk fibroin hydrogel with reversible sol–gel transition

Abstract: Herein, we prepare a novel silk fibroin hydrogel with a reversible thixotropic gel–sol transition triggered by a facile cycled shearing and resting procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 57 publications
4
65
0
Order By: Relevance
“…The results indicated that the hydrophilicity of the blended films improved with increasing the regenerated silk fibroin proportions. The observation demonstrated that the regenerated silk fibroin has significant influence on the wettability of the blended surfaces, which can be explained by the entanglement of RSF molecules and the exposure of their hydrophilic groups, which may be arranged on the surface of RSF chains [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the hydrophilicity of the blended films improved with increasing the regenerated silk fibroin proportions. The observation demonstrated that the regenerated silk fibroin has significant influence on the wettability of the blended surfaces, which can be explained by the entanglement of RSF molecules and the exposure of their hydrophilic groups, which may be arranged on the surface of RSF chains [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the 15 mM DMPG–SF hydrogels reached the failure point at the lowest strain value when compared with the other formulations (Figure h). Yin et al () proposed that not only the beta sheet structure is responsible for the viscoelasticity of SF hydrogels, but also the weak and reversible hydrogen bonds. Certainly, hydrogen bonds can be formed between the polar head of DMPG (Garidel, Blume, & Hübner, ) and SF.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that SS plays a crucial role in the antibacterial process of wound treatment. The sol-gel transition of aqueous solution of SF is a natural process which without an exterior stimulus is quite long, usually a week to a month, which may limit its practical use [323]. Therefore, there are some factors that can stimulate and enhance the gelation kinetics of SF.…”
Section: Silkmentioning
confidence: 99%